Pemanfaatan Terapi Relaksasi Pernapasan untuk Mengurangi Stres pada Ibu Hamil di Puskesmas Nagaswidak Palembang - Tri Restu Handayani; Deby Meitia Sandi (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
Pregnancy affects various aspects of women's physical and mental health. One factor that often occurs in pregnant women is stress, which can affect the health of the mother and fetus. One of the efforts made to overcome stress in pregnant women is relaxation therapy. Relaxation therapy aims to calm the nervous system and help pregnant women overcome anxiety and tension that often occurs during pregnancy. The activity method consists of preparation, implementation and evaluation. The results of the activity were obtained as many as 90% of participants reported an increase in knowledge about stress management during pregnancy, the results of the DASS-21 questionnaire showed a decrease in the average stress score of 30% and all participants were able to perform breathing relaxation therapy techniques correctly based on facilitator observations. This community service activity succeeded in improving the ability of pregnant women to manage stress through breathing relaxation therapy. The output produced can be used for the sustainability of the program at the Health Center.